(untitled) (Fiep Bulletin - online, 2014)
INTRODUCTION :The study it searchs to establish relations between the training of force and the states of humor. OBJECTIVE verify which the acute effect of a session of exercises with weights in the different intensities (55 and 80%) of the maximum load in the different states of mood (tension, anger,vigor, fatigue, depression and mental confusion) in resisted exercises practitioners? MATERIALS And METHODS: The amostral group was constituted by 20 individuals with age enters the 18 25 years. Maximum load test was carried through for repetition, considered and recommended for Weineck (1999), for calculation of the series. A fiche of trainings will have load of 55% of the maximum load (Trainings I) and another one of 80% of the maximum load (Trainings II) for each exercises.During all experiment the group will carry through 3 series I and II, being collected the data daily pay and after test, answering the POMS before and immediately after the ending of each one of the intensities. RESULTS: For 55% you prop up them had presented a significant increase (p<0,05).CONCLUSION The results suggest the training of force with weights in the intensities of 55 % had a negative influence in the states of humor